2012
DOI: 10.1371/journal.pone.0042524
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics in Full-Scale Activated Sludge Bioreactors: Operational and Ecological Factors Driving Community Assembly and Performance

Abstract: The assembling of bacterial communities in conventional activated sludge (CAS) bioreactors was thought, until recently, to be chaotic and mostly unpredictable. Studies done over the last decade have shown that specific, and often, predictable random and non-random factors could be responsible for that process. These studies have also motivated a “structure–function” paradigm that is yet to be resolved. Thus, elucidating the factors that affect community assembly in the bioreactors is necessary for predicting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 78 publications
4
52
1
1
Order By: Relevance
“…Similar results were obtained by Xia [27] who investigated the microbial community structure in response to different ratios of carbon to nitrogen (C/N of 3:1, 5:1, and 10:1) in wastewater sludge. The carbon content as well as C/N ratio of activated sludge collected in 2010 by Subramanian was different from those collected in 2013 in present research, Secondly Valentin [28]reported that biochemical oxygen demand (BOD), influent total suspended solid (TSS), solid retention time (SRT), food/microorganisms (F/M), seem to have the strongest influence on the bacterial communities composition in the bio-reactors. The very low values of F/M in the wastewater treatment plant suggest that the microbial community was starving contributing to high mortality rate among the microbial populations.…”
Section: L-glutamic Acidcontrasting
confidence: 72%
“…Similar results were obtained by Xia [27] who investigated the microbial community structure in response to different ratios of carbon to nitrogen (C/N of 3:1, 5:1, and 10:1) in wastewater sludge. The carbon content as well as C/N ratio of activated sludge collected in 2010 by Subramanian was different from those collected in 2013 in present research, Secondly Valentin [28]reported that biochemical oxygen demand (BOD), influent total suspended solid (TSS), solid retention time (SRT), food/microorganisms (F/M), seem to have the strongest influence on the bacterial communities composition in the bio-reactors. The very low values of F/M in the wastewater treatment plant suggest that the microbial community was starving contributing to high mortality rate among the microbial populations.…”
Section: L-glutamic Acidcontrasting
confidence: 72%
“…Sixtythree families, representing 79 to 91% of the classified sequences, including Rhodocyclaceae, Xanthomonadaceae, Verrucomicrobiaceae, Nitrosomonadaceae, Alcaligenaceae, and Cytophagaceae, were commonly shared by all samples. Most of the shared families were also shared in many other studies (3,24).…”
Section: Resultsmentioning
confidence: 63%
“…Thus, the declining trend in WWTP microbial community richness might also be influenced by the climatic conditions at high elevations, which are characterized by more extreme temperature fluctuations, low air pressure, and stronger UV radiation. It has been reported that the amounts of endemic stress genes, such as 24 genes responsive to extreme temperature stress and the obgE gene for the response to radiation stress, are enriched in the microbial community on the Tibetan grassland (12). This implies that fewer and fewer bacteria can adapt to the extreme physiological challenges on the Tibetan Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…The second point is related to functional redundancy. The application of molecular methods has permitted scientists to show that numerous microbial species can carry out the same biochemical functions during wastewater treatment (He et al, 2010;Hesselsoe et al, 2009;Siripong and Rittmann, 2007;Valentin-Vargas et al, 2012). This redundancy permits COD and nutrient removal to continue in the presence of inhibitors; more resistant subgroups substitute for those that are impaired.…”
Section: The Effect Of Malathion On the Microbial Community In Activamentioning
confidence: 99%